KEBIJAKAN PENGELOLAAN PERIKANAN TANGKAP BERBASIS KEBERLANJUTAN MEWUJUDKAN INDONESIA SEBAGAI POROS MARITIM DUNIA - Indra Yulianingsih (Legality : Jurnal Ilmiah Hukum, 2016)
Management of fish resources (SDI) as a source of natural resources devoted to the people's welfare. Control of the fish resources are directed to the achievement of benefits for the greater prosperity of the people. Fisheries sector can serve as a leading sector in an effort to make Indonesia as the world's maritime axis. Therefore, it must be realized that fisheries management with reference to the principles of sustainable development of marine resources by basing on Agenda 21 of the UN Conference of 1992 on Environment and Development, or the Earth Summit in Rio de Janeiro, Brazil. For that, we need an improvement in the regulation of marine policy. Rights-based Licensing system or rights-based access (allocation of rights to use formal) is an alternative that should be explored, so that everyone has equal access without an incentive to maintain its sustainability.